2019
DOI: 10.1002/cncr.32628
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose chemotherapy plus peripheral blood stem cell transplantation for patients with relapsed germ cell tumors and active brain metastases

Abstract: Background The optimal management of progressive brain metastases in patients with germ cell tumors (GCTs) remains unsettled. This study reports the management of 25 consecutive patients with relapsed GCTs and progressive brain metastases undergoing high‐dose chemotherapy (HDCT) with peripheral blood stem cell transplantation (PBSCT) at Indiana University from 2006 to 2016. Methods All patients were planned to undergo HDCT, which consisted of carboplatin at 700 mg/m2 on days 1 to 3 plus etoposide at 750 mg/m2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It is well known that survival rates in GCT patients with BM are poor. Published data that are based on retrospective studies and with small sample sizes have reported a 2-year OS of 20.7%,9 a 3-year OS of 34.6%,22 and a median OS of 21.8 months 12. These published rates, however, consider all types of treatment including local, conventional, or HDCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that survival rates in GCT patients with BM are poor. Published data that are based on retrospective studies and with small sample sizes have reported a 2-year OS of 20.7%,9 a 3-year OS of 34.6%,22 and a median OS of 21.8 months 12. These published rates, however, consider all types of treatment including local, conventional, or HDCT.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, an improvement in OS was not observed in the population with BM at diagnosis. More recently, Kalra et al 12 reported data from 25 patients with relapsed GCT and progressive central nervous system metastases who underwent HDCT. With a median follow-up of 24.5 months (0.4 to 117 mo), 11 patients (44%) were alive, with no evidence of disease.…”
mentioning
confidence: 99%
“…Studies have shown that SCLC patients with progression after intravenous treatment with an EP regimen still show benefit from oral therapy with etoposide capsules (18). Furthermore, a promising stage II clinical trial reported promising results for patients with germ cell tumors after the oral administration of etoposide capsules, with a lower-than-expected tumor recurrence rate (19).…”
Section: Introductionmentioning
confidence: 99%
“…This patient was treated taking the same aforementioned prophylactic measures; he did not develop major complications during the aplasia phase. The two patients are now well and without evidence of disease [5, 6].…”
mentioning
confidence: 99%